High and low imagers and hemisphere differences in recognition memory performance for picture and word stimuli - Dacko, Wolodymyr (University of Ottawa (Canada), 1973)
Abstract not available.
Keywords: Psychology, Psychobiology.; Psychology, Cognitive.